2020
DOI: 10.3390/ma13245657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Finishing Systems on Surface Roughness and Gloss of Full-Body Bulk-Fill Resin Composites

Abstract: Background: In this study, we assess the effect produced on roughness and gloss of full-body bulk-fill materials by different finishing and polishing systems. Methods: Four full-body bulk-fill materials were tested: SonicFill2 (SF), Filtek Bulk Fill Posterior Restorative (FB), Tetric EvoCeram bulk-fill (EC), and Fill-Up! (FU). Sixty discs per material (2 mm in thickness and 7 mm in diameter) were obtained and randomly assigned (n = 15) to four finishing and polishing methods: Sof-Lex Spiral Wheels (SW), HiLust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 27 publications
0
43
0
7
Order By: Relevance
“…A smooth surface is important in every restorative treatment to reduce biofilm formation. It lends better esthetics, patient acceptance, and clinical success [ 45 ]. Al Moaleem et al [ 46 ] concluded that the presence of smooth restoration, as well as oral prostheses, clinically minimizes adherence and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…A smooth surface is important in every restorative treatment to reduce biofilm formation. It lends better esthetics, patient acceptance, and clinical success [ 45 ]. Al Moaleem et al [ 46 ] concluded that the presence of smooth restoration, as well as oral prostheses, clinically minimizes adherence and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Surface roughness and hydrophobicity (surface free energy) are considered the most important factors [ 20 , 21 , 22 ]. It is worth noting that a fundamental parameter is the materials’ chemical composition, a slight change in which affects both the microbiological characteristics [ 12 , 23 ] and the possibility of achieving the smoothest surface [ 24 , 25 ]. Studies have also revealed that the quality of additive manufacturing and the surface roughness of the samples are significantly affected by the printing parameters (print orientation, layer thickness, localization of supporting structures, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Por isto, esta etapa clínica deve ser seguida indispensavelmente pelo polimento, pois a região porosa da restauração pode servir como retenção para o acúmulo de biofilme, inflamação gengival e contribuem para a formação de cáries secundárias. 29 Desta maneira, o acabamento e polimento são essenciais pra a estética e saúde periodontal, porque atuam minimizando a proliferação de bactérias nas rugosidades, devolvem a anatomia perdida e estabelecem uma superfície polida e brilhosa, possibilitando assim um aspecto estético, semelhante aos dos dentes adjacentes. 30 Observa-se que por meio do plano de tratamento proposto foi possível devolver a estética e função bucal da paciente, com uma reabilitação oral utilizando a resina unicromática que possibilitou um menor custo e otimizou o tempo clínico.…”
Section: Discussionunclassified